2019
DOI: 10.1111/cdev.13277
|View full text |Cite
|
Sign up to set email alerts
|

Observed Profiles of Infant Temperament: Stability, Heritability, and Associations With Parenting

Abstract: Profiles of infant temperament were derived from 990 infants at 6 and 12 months of age using observed measures from the Laboratory Temperament Assessment Battery. Mothers and fathers completed questionnaires measuring parent affect and stress. Four profiles emerged at each age (typical, low negative, withdrawn/inhibited, and positive/active or low reactive) using latent profile analysis. Temperament profiles show some evidence of stability and heritability, particularly for the withdrawn/inhibited group. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
5
28
0
Order By: Relevance
“…In infancy, NA is thought to encompass distinct facets of sadness, fear, frustration/irritability, and falling reactivity or rate of recovery from distress (Table 1). Typically, these emotional states are inferred by caregivers or other observers on the basis of infant behavioral patterns in response to specific contextual cues, commonly associated with each emotional state (Planalp & Goldsmith, 2019). While the extent to which observers can accurately infer infant emotional experience is unclear (Barrett et al, 2019), there is some evidence that these behavioral patterns differ in expected ways in their situational triggers, neurobiological correlates and mental health outcomes, and therefore may act as discrete behavioral markers of risk (Clauss & Blackford, 2012;Kagan et al, 1999Kagan et al, , 2007Planalp & Goldsmith, 2019;E.…”
Section: Introductionmentioning
confidence: 99%
“…In infancy, NA is thought to encompass distinct facets of sadness, fear, frustration/irritability, and falling reactivity or rate of recovery from distress (Table 1). Typically, these emotional states are inferred by caregivers or other observers on the basis of infant behavioral patterns in response to specific contextual cues, commonly associated with each emotional state (Planalp & Goldsmith, 2019). While the extent to which observers can accurately infer infant emotional experience is unclear (Barrett et al, 2019), there is some evidence that these behavioral patterns differ in expected ways in their situational triggers, neurobiological correlates and mental health outcomes, and therefore may act as discrete behavioral markers of risk (Clauss & Blackford, 2012;Kagan et al, 1999Kagan et al, , 2007Planalp & Goldsmith, 2019;E.…”
Section: Introductionmentioning
confidence: 99%
“…Shared environmental factors were strongest for the Regulated, Typical Reactive profile and were also present for the Dysregulated, Negative Reactive profile (Scott et al, 2016). In a profile analysis of observed behavior from the Lab-TAB at 6 and 12 months of age, we again identified four profiles, with the strongest stability and genetic contribution in the Withdrawn/Inhibited profile (Planalp & Goldsmith, 2019). Thus, our project views dimensional and categorical (profile) approaches as complementary and examines both types of measures with biometric approaches.…”
Section: Studies Of the Genetics Of Temperamental Developmentmentioning
confidence: 80%
“…Children who exhibited atypical anger in infancy showed more behavior problems than children who exhibited increasing anger, though only when family stress was low (Brooker et al, 2014). In a second study identifying temperament profiles at 6 and 12 months, fathers reported higher stress levels when infants were more Withdrawn/Inhibited , and less stress when infants were identified as Low Negative (Planalp & Goldsmith, 2019). In the same sample, at 3 years of age, correlates of mother and father parenting behaviors during a dyadic interaction differed depending on parent factors: fathers were more sensitive with their children when marital quality was higher, and mothers were more sensitive when her own positive affect was higher.…”
Section: Roles For Environmental Factors and Gene–environment Interplaymentioning
confidence: 99%
“…Given the very early (4-weeks old) temperament measure used here, we posit that this may be due to the relative instability of child temperament in the first months of life (Beekman et al, 2015). Indeed, child temperament is thought to stabilize later in development (Roberts & Del Vecchio, 2000) and may be a stronger predictor of later child outcomes and parenting behaviors from 9 (Planalp & Goldsmith, 2019). Moreover, temperamental factors may play a greater role in parenting at older ages with increased child autonomy and noncompliance (Kuczynski & Kochanska, 1990), which may explain findings in the previous MLM differential treatment literature (Jenkins et al, 2003;O'Connor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%